Characterization of a Novel High Internal Phase Pickering Emulsions Stabilized by Soy Protein Self-Assembled Gel Particles - Bi, Chong-hao; Chi, Shang-yi; Zhou, Tong; Wang, Xue-ying; Zhang, Jia-yi; Huang, Zhi-gang; Gao, Fei (Frontiers in Nutrition, 2021)
In this paper, a novel high-internal-phase Pickering emulsion (HIPPE) prepared by acid-induced self-assembly SPI gel (A/S-SPIG) was investigated. The steady-state shear test results showed that all HIPPEs were typical shear thinning emulsion, which could form stable emulsion (0.2–1.2% SPI concentration). The network structure of HIPPE stabilized by A/S-SPIG particles (0.2–1.2% SPI concentration) was continuously enhanced with increasing SPI concentration. The high concentration of SPI particles increased the crystallization temperature of the stabilized HIPPE. Meanwhile, at a concentration of 1.2%, HIPPE has the best cohesive property and stability against delamination due to weakened mobility. In conclusion, A/S-SPIG was proved excellent HIPPE stabilized particle.